2008
DOI: 10.1159/000135663
|View full text |Cite
|
Sign up to set email alerts
|

7-Ketocholesterol Upregulates Interleukin-6 via Mechanisms That Are Distinct from Those of Tumor Necrosis Factor-α, in Vascular Smooth Muscle Cells

Abstract: This study investigated the effects of 7-ketocholesterol on interleukin (IL)-6 expression in vascular smooth muscle cells (VSMC). Among the 7 IL examined, only IL-6 transcript was increased by 7-ketocholesterol treatment in human aorta smooth muscle cells. IL-6 transcripts increased up to 24 h after treatment with 7-ketocholesterol, and this effect was profoundly repressed by treatment with p38 MAPK inhibitors and to a lesser extent JNK inhibitors. 7α-Hydroxycholesterol, 27-hydroxycholesterol or cholesterol, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…For instance, ANG II rapidly induces IL-6 mRNA expression in both vascular SMCs and cardiac fibroblasts, with the peak induction at ϳ30 min to 1 h (44,45); however, thrombin stimulates a quick induction of IL-6 mRNA expression in vascular SMCs, with the peak induction at ϳ30 min to 1 h, whereas in lung fibroblasts and blood monocytes, thrombin induces delayed IL-6 mRNA accumulation, with an induction peak at ϳ6 -12 h (30,48). A recent study (49) showed that oxysterol 7-ketocholesterol induces IL-6 mRNA expression in vascular SMCs in a delayed pattern as well, peaking at 24 -48 h (49). The regulation mechanisms in response to various stimuli in these different cell types are also different.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ANG II rapidly induces IL-6 mRNA expression in both vascular SMCs and cardiac fibroblasts, with the peak induction at ϳ30 min to 1 h (44,45); however, thrombin stimulates a quick induction of IL-6 mRNA expression in vascular SMCs, with the peak induction at ϳ30 min to 1 h, whereas in lung fibroblasts and blood monocytes, thrombin induces delayed IL-6 mRNA accumulation, with an induction peak at ϳ6 -12 h (30,48). A recent study (49) showed that oxysterol 7-ketocholesterol induces IL-6 mRNA expression in vascular SMCs in a delayed pattern as well, peaking at 24 -48 h (49). The regulation mechanisms in response to various stimuli in these different cell types are also different.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ROS in these cells has been supported by studies that used antioxidants to abolish their action ( 8, 109 , 110 ). Another mechanism described for the proinfl ammatory role of 7KCh in VSMCs is the translocation of the HuR protein from the nucleus to the cytoplasm ( 103 ). HuR is an RNA-binding protein that …”
Section: Pharmacological Properties Of 7kchmentioning
confidence: 99%
“…MAPKs play important roles in VSMC secretion of cytokines and chemokines [15,16]. We investigated whether MAPKs affected nucleotide-mediated CCL2 secretion.…”
Section: Up-regulationmentioning
confidence: 99%